A Dual Role of Complement Activation in the Development of Fulminant Hepatic Failure Induced by Murine-Beta-Coronavirus Infection - Fang, Yingying; Guo, Yan; Gao, Tongtong; Han, Xuelian; Jiang, Yuting; Li, Min; Xue, Wei; Yang, Binhui; Cui, Yujun; Sun, Shihui; Zhao, Guangyu (Frontiers in Cellular and Infection Microbiology, 2022)
With the epidemic of betacoronavirus increasing frequently, it poses a great threat to human public health. Therefore, the research on the pathogenic mechanism of betacoronavirus is becoming greatly important. Murine hepatitis virus strain-3 (MHV-3) is a strain of betacoronavirus which cause tissue damage especially fulminant hepatic failure (FHF) in mice, and is commonly used to establish models of acute liver injury. Recently, MHV-3-infected mice have also been introduced to a mouse model of COVID-19 that does not require a Biosafety Level 3 (BSL-3) facility. FHF induced by MHV-3 is a type of severe liver damage imbalanced by regenerative hepatocellular activity, which is related to numerous factors. The complement system plays an important role in host defense and inflammation and is involved in first-line immunity and/or pathogenesis of severe organ disorders. In this study, we investigated the role of aberrant complement activation in MHV-3 infection-induced FHF by strategies that use C3-deficient mice and intervene in the complement system. Our results showed that mice deficient in C3 had more severe liver damage, a higher viral load in the liver and higher serum concentrations of inflammatory cytokines than wild-type controls. Treatment of C57BL/6 mice with C3aR antagonist or anti-C5aR antibody reduced liver damage, viral load, and serum IFN-γ concentration compared with the control group. These findings indicated that complement system acts as a double-edged sword during acute MHV-3 infection. However, its dysregulated activation leads to sustained inflammatory responses and induces extensive liver damage. Collectively, by investigating the role of complement activation in MHV-3 infection, we can further understand the pathogenic mechanism of betacoronavirus, and appropriate regulation of immune responses by fine-tuning complement activation may be an intervention for the treatment of diseases induced by betacoronavirus infection.